Optimización en el proceso de recepción de partes y repuestos en la Dirección de la Industria Aeronáutica de la Fuerza Aérea Ecuatoriana (DIAF) de la ciudad de Latacunga. - Hernández Caiza, José Mauricio (2020)
This researching project was carried out in the reception of parts section and spare parts of the enterprise Direction of the Aeronautical Industry from Ecuadorian Air Force DIAF in the Latacunga city, cause of DIAF main economic activity is the maintenance of civil and military aircrafts, for this reason they handle a great amount of parts and spare parts of aeronautical purpose, which ones are received following requirements of authorities and aeronautical companies. The main objective of this project focused in improving this process, cause of enterprise had a generalized but not specific process, for this reason, a standarded time of activities and productivity was unknown according to the resources in labor employed, by affecting many times to the maintenance planning fulfillment. According to the acquired knowledge in the industrial engineering career and with the support of educational staff, the present research was made in the best way, by using the methodologies and techniques of methods engineering. In the first part was carried out a survey of the initial status of the process, which results were represented in flow and route diagrams process; then we made a time study in this state, to determine the standard time and productivity; next we purpose an improved method, with the reduction of standard time and with the increase of the productivity. The improved method was standardized in a procedure manual to the parts reception of parts and spare parts in DIAF.